Transformasi Digital UMKM: Program Upskilling Digital Marketing di Pantai Jerman, Kuta - Bali - Saputra, I Gusti Ngurah Widya Hadi; Wijaya, Gede Crisna; Lestari, Ni Putu Nina Eka (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
Digital transformation and marketing are crucial for the sustainability and growth of MSMEs in Pantai Jerman, Kuta, Bali. However, many local MSMEs still need to utilize digital technology fully. This community service activity aims to enhance awareness and understanding of digitalization and digital marketing through face-to-face socialization and mentoring. The program includes education on the benefits of digital marketing, techniques for using social media, and digital tools for business promotion. As a result, MSME operators' awareness and understanding increased, and many began utilizing digital technology for business promotion. Support in the form of a mini digital studio was also provided to assist in creating digital content. This program successfully promoted digital transformation among MSMEs in Pantai Jerman, positively impacting their business sustainability and growth.